2022
DOI: 10.1177/08982643221086336
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Traumatic Events on Mental Health Among Older African American and Black Caribbean Adults

Abstract: Objectives: This study examined the frequency and impact of traumatic events on the mental health of older African American and Black Caribbean adults. Methods: The current study used data from the National Survey of American Life of 1,135 African American and 426 Black Caribbean adults aged 50 and older. Analysis examined the impact of traumatic events on both positive (i.e., happiness and life satisfaction) and negative (i.e., depressive symptoms, psychological distress, and 12-month anti-depressant use) dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…There is evidence from another study of PTSD and aging in the general U.S. population (Reynolds et al, 2016) that older adults report lower prevalence of types of traumatic events (e.g., interpersonal violence and sexual assault) that confer PTSD risk in Black women (Lacey et al, 2021). In another paper in this issue, post-traumatic events (PTE) in older Black adults were found to be associated with depressive symptoms and psychological distress (Brooks et al, 2022); when screened and found in the 12-months prior to the interview, PTEs were treated with anti-depressants. The most commonly experienced types of PTEs in their study were having someone close die unexpectedly, seeing someone badly injured, being mugged, having a life-threatening illness, and being in a life-threatening car accident (Brooks et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence from another study of PTSD and aging in the general U.S. population (Reynolds et al, 2016) that older adults report lower prevalence of types of traumatic events (e.g., interpersonal violence and sexual assault) that confer PTSD risk in Black women (Lacey et al, 2021). In another paper in this issue, post-traumatic events (PTE) in older Black adults were found to be associated with depressive symptoms and psychological distress (Brooks et al, 2022); when screened and found in the 12-months prior to the interview, PTEs were treated with anti-depressants. The most commonly experienced types of PTEs in their study were having someone close die unexpectedly, seeing someone badly injured, being mugged, having a life-threatening illness, and being in a life-threatening car accident (Brooks et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In another paper in this issue, post-traumatic events (PTE) in older Black adults were found to be associated with depressive symptoms and psychological distress (Brooks et al, 2022); when screened and found in the 12-months prior to the interview, PTEs were treated with anti-depressants. The most commonly experienced types of PTEs in their study were having someone close die unexpectedly, seeing someone badly injured, being mugged, having a life-threatening illness, and being in a life-threatening car accident (Brooks et al, 2022). The good news is that despite experiencing such PTEs they did not go on in large numbers based on our results to advance to PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…As people enter adulthood, their experiences and exposures to new adverse events can also have long-term impacts. Exposure to adversity across the life course has the potential to profoundly impact cognitive, mental, and physical health [8,9,[25][26][27][28][29]. For example, having a close relative who is addicted to drugs or alcohol has been found to have lasting effects on an individual's emotional well-being, often through stress and family strain [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Work by Brooks et al (2022) provides one of the first examinations of traumatic events among the older Black American population. They found that 8 out of 10 older African Americans and Black Caribbeans have had at least one traumatic event in their lifetime.…”
Section: Introductionmentioning
confidence: 99%